Multiple episodes of hypoglycemia secondary to an insulinoma: case report - Vázquez-Lara, Sergio E.; Guerrero-Arroyo, Aracely A.; Landeros-Muñoz, Manuel; Sánchez-Lara, Luis F.; Núñez-Arroyo, Bryan; Valdes-Ramos, R. L.; Flores-Villalba, Eduardo (International Surgery Journal, 2023)
Within the group of pancreatic neuroendocrine tumors, insulinomas are the most frequent functioning tumors, representing 42% with an annual incidence of 0.4 cases per 100,000 inhabitants and exhibiting poor survival of less than 5 years. We report the case of a 57-year-old male with episodes of hypoglycemia of one year of evolution. Abdominal computed tomography reported a 3.5×3.6 cm mass in the neck of the pancreas. Surgery is the mainstay of treatment for insulinomas. Different studies have shown that the presence of these tumors is more frequent in patients undergoing post-mortem examinations. Diagnosis is usually late due to non-specific symptoms and is clinically based on the "Whipple’s triad", as well as imaging and laboratory studies. Surgery is the mainstay of treatment for insulinomas. The minimally invasive procedure is an effective modality due to its benefits, however, it continues to be below conventional surgical management. In addition, the study of an intraoperative ultrasound helps to preserve the largest viable pancreatic tissue to avoid later complications.